A Driver and Control Method for Primary Stator Discontinuous Segmented-PMLSM - Mingyi Wang (MDPI AG, 2021)
In recent years, with the development of the permanent magnet linear synchronous motor (PMLSM), the application of PMLSM has not been limited only to the high-end equipment field; the primary stator discontinuous segmented-PMLSM (DSPMLSM), which consists of multiple primary stators and one mover, has also been applied in long-distance transportation systems, such as electromagnetic launch, high precision material transport, etc. Compared with the symmetry phase parameters of conventional PMLSM, the stationary electrical parameters vary when the mover enters and leaves the primary stators (the inter-segment region). At the same time, due to the sectional power supply, there will be primary suction or pulling force when the mover enters and exits the inter-segment region, which will lead to large thrust fluctuation and result in lager position error. This paper proposed a related drive and control strategy about the DSPMLSM system, which improved the position tracking accuracy during the full range of DSPMLSM. First, the parameter variation between stator segments has been analyzed through finite element simulation of DSPMLSM. Then, a double closed-loop series control structure of position-current is designed, in which a PI-Lead controller was adopted for the position loop and a PI controller was adopted for the current loop. In order to improve the position tracking accuracy of DSPMLSM, a thrust fluctuation extended state observer (TFESO) was adopted to observe and compensate the complex thrust disturbances such as cogging force, friction and other unmodeled thrust fluctuation. At last, the DSPMLSM experimental stage was established, and the experimental results show that the proposed driver and control theory can effectively improve the position tracking accuracy of the whole stroke of DSPMLSM.